Building national consensus on experiences of care - Anna Baranski; Neil Churchill; Sophie Staniszewska (The Beryl Institute, 2015)
The NHS in England is measured against specific indicators that focus on 'ensuring that people have a positive experience of care,' yet there was a lack of organisational alignment across the new national health and care organisations regarding their understanding of what constitutes a positive experience of care. This represents a major barrier to achieving an aligned and consistent system-wide approach to improving experiences. To address the need to create national alignment in definition and approach, we worked with the Patient Experience Sub-group of the National Quality Board to develop consensus on how national organisations define 'experience of care' and what constitutes a good experience of care, drawing on relevant evidence and guidance. Working in collaboration, we developed a 'Narrative' to describe this consensus and highlight resources and examples of good practice on improving experiences of care for the wider system, including commissioners and providers, to support broader improvement and implementation efforts.